The role of national and religious minorities in the 2021 Iraqi elections - Fadhil Malik Fadhil Zwain (Periodica Journal, 2022)
The issue of minorities occupies great importance in the countries of the world, especially the countries whose population consists of multiple nationalities, and this issue has become of dimension that touches the core of the security and stability of countries. The issue of minorities being subjected to oppression has become a matter of reality, which made the protection of minorities one of the important issues. The danger of restrictions on the minority appears, in that it doubles its affiliation with the country in which it lives and resorts to the neighboring countries with the geographical extension of the minority, which feeds its separatist tendency. Many minorities have relations and extensions that go beyond the internal scope of the state due to their national, linguistic or religious connection to other countries with similar characteristics
Keywords: multiple nationalities; minorities